1991
DOI: 10.1002/eji.1830210425
|View full text |Cite
|
Sign up to set email alerts
|

The role of oil and agalactosyl IgG in the induction of arthritis in rodent models

Abstract: The proportion of agalactosyl IgG [Gal(O)] is raised in human rheumatoid arthritis and tuberculosis. We report here that injection of pristane into the peritoneal cavities of mice on days 0 and 50, which is known to induce plasmacytomas and arthritis, also induced a rise in the proportion of Gal(O), correlating with a simultaneous rise in the level of IgG antibody binding to the 65-kDa heat-shock protein of Mycobacterium bovis (hsp65). Arthritis developed in a proportion of those CBA/Igb mice with the highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 32 publications
2
31
0
Order By: Relevance
“…In this disease the IL-6 synthesis rate in the joint is increased as is the case for its physiological inducer IL-1 (Van Damme et al, 1987b). Interestingly, the IgG produced in rheumatoid arthritis (Rademacher et al, 1988a) and transgenic IL-6 mice (Rook et al, 1991), as well as in Castleman's disease, cardiac myxoma and mesangial proliferative glomerulonephritis all have the agalactosyl IgG glycoform type (unpublished data). These results suggest that IL-6 may affect either the glycosyltransferase levels of B cells or cause a unique subset of B cells with this phenotype to secrete at a higher rate.…”
Section: -1mentioning
confidence: 88%
See 1 more Smart Citation
“…In this disease the IL-6 synthesis rate in the joint is increased as is the case for its physiological inducer IL-1 (Van Damme et al, 1987b). Interestingly, the IgG produced in rheumatoid arthritis (Rademacher et al, 1988a) and transgenic IL-6 mice (Rook et al, 1991), as well as in Castleman's disease, cardiac myxoma and mesangial proliferative glomerulonephritis all have the agalactosyl IgG glycoform type (unpublished data). These results suggest that IL-6 may affect either the glycosyltransferase levels of B cells or cause a unique subset of B cells with this phenotype to secrete at a higher rate.…”
Section: -1mentioning
confidence: 88%
“…Transgenic IL-6 mice are characterized by kidney disease and plasmacytosis (Suematsu et al, 1989) and IL-6 is a growth factor for murine plasmacytomas (Van Damme et al, 1987b). Pristane injected into mice leads to high constitutive levels of IL-6 and contributes to myeloma formation (Nordan and Potter, 1986;Rook et al, 1991).…”
Section: -1mentioning
confidence: 99%
“…This role of IL-6 has been clearly demonstrated by the clinical improvement of RA patients who undergo anti-IL-6 treatment (Wendling et al, 1993) and by the resistance of IL-6 knockout mice to antigen-induced experimental arthritis (Boe et al, 1999). Moreover, susceptibility to PIA has been shown to be associated with elevated levels of agalactosyl IgG resulting from unregulated IL-6 production (Rook et al, 1991). In agreement with these data, our results showed high levels of IL-6 production when arthritis was well established in AIRmax mice injected with pristane (Fig.…”
Section: Figmentioning
confidence: 99%
“…In susceptible inbred lines of mice such as BALB/c (Portter and Wax, 1981) and CBA Igh b , 15 to 25% developed inflammation of the ankle and wrist joints approximately 200 days after pristane injection (Thompson and Elson, 1993). Susceptibility to PIA has been shown to be associated with elevated levels of agalactosyl IgG caused by unregulated interleukin (IL)-6 production (Rook et al, 1991) and with major histocompatibility complex genes (the H-2 q , H-2 d , and H-2 r alleles are susceptible) (Wooley et al, 1989). Such susceptibility also seems to be CD4 ϩ T (helper T cell type 1 [Th1] or Th2) cell dependent (Stasiuk et al, 1997).…”
Section: Introduction Dmentioning
confidence: 99%
“…In susceptible inbred lines of mice such as BALB/c [6] and CBA Igh b [7], 15 % to 25 % of mice developed inflammation of the ankle and wrist joints around 200 days after pristane injection [8]. Susceptibility to PIA has been shown to be associated to elevated levels of agalactosyl IgG raised by IL-6 unregulated production [9], to major histocompatibility complex (MHC) genes (H-2q,d,r alleles are susceptible) [10] and to be CD4 + T cells (Th) dependent [11]. It was demonstrated that PIA incidence was accompanied by markedly elevated humoral and cellular responses to mycobacterial 65-kDa heat shock protein (hsp65) [12], and recently it was suggested that the protection against PIA is mediated by Th2-associated cytokines produced after hsp65 preimmunization [13].…”
Section: Introductionmentioning
confidence: 99%